Developmental Expression of a Trypanosoma cruzi Phosphoinositide-Specific Phospholipase C in Amastigotes and Stimulation of Host Phosphoinositide Hydrolysis - de Paulo Martins, Vicente (American Society for Microbiology (ASM), 2010)
Phosphoinositide phospholipase C (PI-PLC) plays an essential role in cell signaling. A unique Trypanosoma cruzi PI-PLC (TcPI-PLC) is lipid modified in its N terminus and localizes to the outer surface of the plasma membrane of amastigotes. We show here that TcPI-PLC is developmentally regulated in amastigotes and shows two peaks of surface expression during the developmental cycle of T. cruzi, the first immediately after differentiation of trypomastigotes into amastigotes and the second before differentiation of amastigotes into trypomastigotes. Surface expression of TcPI-PLC coincides with phosphatidylinositol 4,5-bisphosphate (PIP(2)) depletion in the host cell membrane and with an increase in the levels of its product, inositol 1,4,5-trisphosphate. During extracellular differentiation, PI-PLC is secreted into the incubation medium. Maximal early expression of TcPI-PLC on the surface of amastigotes and PIP(2) depletion coincide with host cytoskeletal changes, Ca(2+) signaling, and transcriptional responses described previously. The presence of TcPI-PLC on the outer surface of the plasma membrane of the parasite and the capacity to be secreted and to alter host phospholipids are novel mechanisms of the host-parasite interaction.